Jalan Panjang Konstitusi Indonesia: Perspektif Politik dan Hukum - Basuki, Udiyo (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The constitution was born from the understanding of constitutionalism which limits state power on the one hand and guarantees people's rights on the other hand through constitutional rules. The constitution is where all laws and regulations must depend. Therefore, studying the journey of the Indonesian constitution is important for at least three reasons, namely, first, three constitutions were once in force in Indonesia, namely the 1945 Constitution, the 1949 RIS Constitution and the 1950 Temporary Constitution. From here it can be seen that there was a replacement of the constitution. Second, the 1945 Constitution has undergone 4 amendments in the reform era. And third, there are pros and cons to the results of the amendments in question. With a focus on the government period which is divided into 3 orders, namely the Old Order, the New Order and the Reformation Order, this writing, which is inspired by the increasing constitutional awareness of citizens, wants to study the dynamics of the journey of the constitution from a political and legal perspective